Financing sustainable agriculture and mitigation - Alforte, A; Matias, D; Munden, L; Perron, J (2013)
Key messages: - Smallholder farmers and forestry producers have a crucial role to play in food security, sustainable land use and emissions reductions initiatives. - Producers and investors alike require appropriate incentive structures to facilitate participation in sustainable land use initiatives. - A networked financing approach—Inari—may provide an innovative response to financing sustainable land use via intelligent diversification and addressing the finance needs of smallholders. - Diversification requires the development of a more holistic risk model for investment in smallholder agriculture and forestry, which will be tested in a number of developing countries in 2013 and 2014.